2015
DOI: 10.1039/c5cc06424d
|View full text |Cite
|
Sign up to set email alerts
|

Alkynol natural products target ALDH2 in cancer cells by irreversible binding to the active site

Abstract: Falcarinol and stipudiol are natural products with potent anti-cancer activity found in several vegetables. Here, we use a chemical proteomic strategy to identify ALDH2 as a molecular target of falcarinol in cancer cells and confirm enzyme inhibition via covalent alkylation of the active site. Furthermore, the synthesis of stipudiol led to the observation that ALDH2 exhibits preference for alkynol-based binders. Inhibition of ALDH2 impairs detoxification of reactive aldehydes and limits oxidative stress respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 29 publications
1
45
0
Order By: Relevance
“…Thus, with synthetically optically active diynols in hand, we evaluated their antiproliferative effects on the HepG2 and HeLa cancer cells. As natural falcarinol exhibited no cytotoxicity toward HepG2 cancer cells with an undetectable half maximal inhibitory concentration (IC 50 ) value, we selected 5‐fluorouracil (5‐FU) as a positive control (Tables S4 and S5), which is currently widely used in clinical therapeutics as an anticancer drug.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, with synthetically optically active diynols in hand, we evaluated their antiproliferative effects on the HepG2 and HeLa cancer cells. As natural falcarinol exhibited no cytotoxicity toward HepG2 cancer cells with an undetectable half maximal inhibitory concentration (IC 50 ) value, we selected 5‐fluorouracil (5‐FU) as a positive control (Tables S4 and S5), which is currently widely used in clinical therapeutics as an anticancer drug.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Sieber et al. reported that a falcarinol‐based probe molecule could be used as a selective tool to target a specific protein in cancer cells, in which a conserved preference of a chiral propargyl alcohol by irreversibly binding to Cys of the active site was observed with sterically selective catalytic inhibition . To investigate whether there was stereoselective cytotoxic activity against HepG2 and HeLa cancer cells, we studied the anticancer activity of enantiomers ( R )‐ 1 , ( R )‐ 2 , ( R )‐ 3 , and ( S )‐ 14 against HepG2 and HeLa cells (Table , entries 1–4 and Table S5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we showed that agelasine D (a marine spongean diterpene alkaloid) binds to the mycobacterial protein BCG3185c (a putative dioxygenase), and we suggested that this protein is a novel drug target against tuberculosis . In addition, some lipid‐like natural products are also known to have unique targets in cancer cells …”
Section: Introductionmentioning
confidence: 99%
“…[8] In addition, some lipid-like natural products are also known to have unique targets in cancer cells. [9,10] The furanosesterterpenef urospinosulin-1 (1)w as originally isolated from the marine sponge Ircinia spinosula. [11] Ta sdemir et al [12] reported that 1 showedw eak anti-proliferative activity against isogenic human colon cancerH CT-116 cells under normoxic conditions, and Erdogan-Orhan et al [13] reported that 1 inhibited CDC25A (cell division cycle 25 homologue Ap hos-Hypoxia-adapted cancer cells in tumors contribute to the pathological progression of cancer.C ancer research has therefore focused on the identification of molecules responsible for hypoxiaa daptation in cancer cells, as well as the development of new compounds with action against hypoxia-adapted cancer cells.…”
Section: Introductionmentioning
confidence: 99%